Adaptation of Latex Diagnosis Parameters Determination using Multiplate Reader and Freeze-Drying Conservation to Support Large-Scale Utilization in Rubber Plantations - Junaidi, Junaidi; Syafaah, Afdholiatus; Aji, Martini; Ismawanto, Sigit; Oktavia, Fetrina; Subandiyah, Siti; Montoro, Pascal; Nuringtyas, Tri Rini (Trends in Sciences, 2024)
The Latex Diagnosis (LD) is performed through the determination of dry rubber (DRC), sucrose (Suc), inorganic phosphorus (Pi) and thiol (RSH) contents. It is carried out through the colorimetric method using a single cuvette spectrophotometer, which is time-consuming and requires a high volume of chemicals. It also needs to be executed as soon as the samples are collected so that limits the adoption of LD. The adaptation of the protocol to a multiplate reader and suitable conservation aimed to overcome the limitations. The experiments were carried out at the Indonesian Rubber Research Institute, Sembawa, Palembang, and Research Center for Biotechnology, Universitas Gadjah Mada, Yogyakarta. Various combinations of solution volumes, adapted from standard protocol, were tested. The closest slope of the standard curve to control was then applied to 7 randomly selected trees. The result showed that for Suc, the composition of 10 µL samples, 30 µL of 2.5 % TCA and 210 µL anthrone reagent was suitable for determination using a multiplate reader. The combination of 40 µL of sample, 85 µL of 2.5 % TCA and 125 µL mL FeSO4 solution was suitable for Pi determination, while 100 µL samples, 5 µL DNTB and 100 µL Tris is recommended for RSH. The measurement using a multiplate reader resulted in comparable contents (average deviations were 1.83, 2.69 and 3.51 % for Suc, Pi, and RSH, respectively), lower time and chemicals consumptions, and a larger number of sample handling compared to single cuvette method. This study also tested the effect of freeze-drying for sample conservation. The result indicated that freeze-drying was able to maintain the Pi level (deviation 0.93 %). However, it increased Suc (deviation 19.43 %) and decreased ascorbate (AsA) significantly (deviation 43.60 %); therefore, freeze-drying might not be suitable for conserving serum samples in the LD method. HIGHLIGHTS Latex diagnosis in Hevea brasiliensis latex can be performed using a multiplate reader with comparable results, lower time and chemicals consumptions and a larger number of sample handling compared to the standard single cuvette method. For sucrose content determination, the combination of 10 µL samples, 30 µL of 2.5 % TCA and 210 µL anthrone reagent is recommended. The combination of 40 µL of sample, 85 µL of 2.5 % TCA and 125 µL FeSO4 solution is suitable for inorganic phosphorus content determination, while 100 µL samples, 5 µL DNTB and 100 µL Tris is suitable thiols content quantification. Conserving latex serum through freeze-drying is able to maintain the inorganic phosphorus content. However, this treatment may lead to an increase in sucrose content and a decrease in the antioxidant content. Freeze-drying may not be suitable for conserving serum samples in the latex diagnosis method. GRAPHICAL ABSTRACT